Beyond the lab coat: methodological challenges in space life sciences - Van Puyvelde, Martine; van den Berg, Nicholas H.; Stas, Lara; Savieri, Perseverence; Corlùy, Hortense; Van Cutsem, Jeroen; Neyt, Xavier; Simonelli, Guido; Pattyn, Nathalie (Frontiers in Physiology, 2025)
As plans for deep space and long-duration missions advance, research in space and space-analog environments is becoming an urgent scientific priority. However, this type of fieldwork poses a unique set of challenges. The development of research methodologies and designs cannot rely on broad evidence base and thus requires scientific judgment and multidisciplinary psychophysiological expertise. Most studies comprise small samples, often lack control groups, sex differences have seldom been directly tested in this area and inter-individual variability is prevalent in this population. Moreover, this research domain is characterized by several exceptional factors that must be addressed. The target population is highly trained and not representative of the general population, demanding adapted study designs and highly sensitive and operationally relevant research tools. To avoid overburdening the already heavy operational schedules of this population, a careful and feasible balance must be established between scientific data quality and acceptable monitoring load. Furthermore, several issues of location, timing, and type of baseline measures must be explicitly considered, while long-term follow-up designs are necessary to assess both recovery and persistent post-mission effects. Major space agencies have indeed identified methodological issues as a knowledge gap in this area. In this review, we provide an overview of these methodological challenges unique to space life sciences and offer solutions where possible. We argue that space research remains feasible despite these constraints, but only when it is approached with the understanding that such fieldwork often requires fundamentally different methods than traditional laboratory science.